OPTIMIZATION OF THE HALAL INDUSTRY SECTOR: THE POTENTIAL OF HALAL MEDIA AND ENTERTAINMENT IN INDONESIA - Andani, Listia; Fathoni, Hamdan; Nurdiansyah, Irdan (Finansha: Journal of Sharia Financial Management, 2024)
This research examines efforts to optimize the halal industry sector in Indonesia, with a particular focus on the potential of halal media and entertainment. The significant growth of the halal industry market presents a substantial opportunity for Indonesia, a nation with a predominantly Muslim population. A qualitative descriptive method is employed to investigate strategies for leveraging the potential of halal media and entertainment in Indonesia. The research emphasizes the analysis of relevant data related to the topic, aiming to enhance the appeal and contribution of the halal media and entertainment sector through a literature review approach.  By conducting an in-depth analysis of consumer trends and industry developments, this study provides a comprehensive perspective on the opportunities and challenges in the development of halal media and entertainment. Special attention is given to regulatory and promotional strategies to maximize the potential of this sector. The findings of this research are anticipated to offer practical guidance for stakeholders in the halal industry, with the objective of reinforcing Indonesia's position as a leader in the global halal industry. The implications of this study include the development of more effective strategies to increase public awareness and industry participation, as well as providing a foundation for policy development that supports the sustainable growth of the halal media and entertainment sector in Indonesia.